Control Beliefs as Regards Fetus Health: Factorial Structure and Reliability of an Adapted Spanish Version of the Fetal Health Locus of Control Scale (FHLC) (Revista de Psicología, 2019)
This study presents the factorial structure and reliability assessment of a Spanish version of the Fetal Health Locus of Control scale, which assesses control beliefs related to fetus health based on the Locus of Control concept coined by Rotter. The scale was administered to women ofchildbearing age (N=130) in educational institutions from Santa Fe city. The adapted version of the scale reveals a three-main-factors structure that correspond to the theoretical constructs on which the original scale is based. Internal consistency assessed by Cronbach’s alpha was adequate, with values of .81 for the FHLCE-D subscale, .75 for the FHLCI subscale and .76 forFHLCE-P subscale. In conclusion, the adapted version of thescale has satisfactory psychometric properties, similar to those of the original one..
Keywords: Locus of Control; Health; Pregnancy.